2015
DOI: 10.1093/tropej/fmv090
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Profile of Kawasaki Disease in Algerian Children: A Single Institution Experience

Abstract: One hundred thirty-three patients (82 boys and 51 girls) with a mean age of 31 months were identified. The most common sign was fever, rash, oral changes and conjunctivitis. The cardiac complications were CAL (22.5%), pericarditis (2%) and myocarditis (1.5%). The independent variable for prediction of CAL was duration of fever >10 days, male gender and platelet count >450,000/mm3 CONCLUSION: The incidence of cardiovascular complications is high. Knowledge of KD among Algerian pediatricians should be enhanced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
4
13
1
Order By: Relevance
“…The first case was 3 year old child while the second was an infant. This is in keeping with epidemiologic studies from Algeria and Japan which have shown that more than 90% of children are less than 5 years of age [ 2 , 5 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The first case was 3 year old child while the second was an infant. This is in keeping with epidemiologic studies from Algeria and Japan which have shown that more than 90% of children are less than 5 years of age [ 2 , 5 ].…”
Section: Resultssupporting
confidence: 87%
“…In Africa, two cases were reported in South Africa in Caucasian children in 1980 but the first case in an African child was reported in Ivory Coast in 1981. Despite of sporadic cases being reported across many countries in Africa, mainly North Africa and the West African region, the epidemiological data for KD is limited for African countries [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of Kawasaki in Tunisia, Morocco, and Algeria has been documented as 0.95, 4.52, and 3.15, respectively [ 17 ]. Boudiaf et al [ 18 ••] reviewed 133 children (82 boys and 51 girls) with KD that were seen at a public hospital in Algeria between 2005 and 2014. Of the 133 patients seen, 131 met the complete criteria for Kawasaki while two demonstrated incomplete criteria.…”
Section: Medium-vessel Vasculitismentioning
confidence: 99%
“…The mean age at diagnosis was 31 months. The commonest signs were fever, rash, oral changes, and conjunctivitis [ 18 ••]. A study from Egypt reported that 6.7% of adults aged 40 years or younger and who underwent angiography for evaluation of possible myocardial ischemia had lesions consistent with antecedent KD [ 19 ].…”
Section: Medium-vessel Vasculitismentioning
confidence: 99%
“…5 Heart complications constitute a significant cause of morbidity in these patients, which may appear in the acute phase (myocarditis, pericarditis, mitral regurgitation, and coronary artery ectasia) or in the subacute phase of the disease (coronary artery aneurysms). 6 Many children, especially infants, do not exhibit all of the above criteria (nontypical or incomplete Kawasaki disease 5 days with fever but < additional four diagnostic criteria). In these patients, heart complications tend to be more frequent.…”
Section: Introductionmentioning
confidence: 99%